A method for producing polycarbonate by a non-phosgene melt transesterification method and polycarbonate
Patent Information
- Application Number
- CN202610821334.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-09
AI Technical Summary
[0004]然而,现有非光气熔融酯交换法在实际工业化应用中仍存在难以兼顾产品性能与原料消耗的技术瓶颈
[0045] 1. This invention optimizes the temperature, pressure, and molar ratio of the prepolymer during the prepolymerization stage, thereby stabilizing the intrinsic viscosity of the prepolymer within an ideal window. This lays a high-quality feed foundation for subsequent polycondensation, significantly improving the notched impact strength of polycarbonate and effectively narrowing the product performance fluctuation range, thus providing dual protection for the product's toughness and consistency.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials, specifically relating to a method for preparing polycarbonate by non-phosgene melt transesterification and the polycarbonate thereof. Background Technology
[0002] Polycarbonate, as an engineering plastic with excellent comprehensive performance, is widely used in high-end fields such as electronics, automotive manufacturing, building materials, medical devices, and optical lenses due to its outstanding impact strength, light transmittance, heat resistance, and dimensional stability. With the continuous improvement of material performance requirements in downstream industries, the market demand for high-toughness, high-purity polycarbonate is increasing, especially in applications with extremely high material reliability requirements such as aerospace, new energy vehicles, and precision optics. Key indicators of polycarbonate, such as impact strength and performance stability, directly determine the product's performance and lifespan. How to reduce raw material consumption and energy waste in the production process while ensuring high product performance has become an important issue that polycarbonate manufacturers must address.
[0003] Non-phosgene melt transesterification has gradually become one of the mainstream technologies for the industrial production of polycarbonate due to its advantages such as avoiding the use of phosgene, relatively simple process, and environmental friendliness. This method uses bisphenol A and diphenyl carbonate as raw materials, generating oligomers through transesterification, followed by pre-condensation and final condensation stages to gradually increase the molecular weight, ultimately yielding the polycarbonate product. The key to this method lies in the parameter matching and process control at each reaction stage, which directly affects the molecular weight distribution, end-group structure, and final properties of the product.
[0004] However, existing non-phosgene melt transesterification methods still face technical bottlenecks in practical industrial applications, making it difficult to balance product performance and raw material consumption. On the one hand, to obtain polycarbonate products with high impact toughness and uniform molecular weight distribution, high-temperature, high-vacuum, and long-duration reaction conditions are often required during the polycondensation stage to fully remove byproducts and promote molecular chain growth. On the other hand, these harsh reaction conditions exacerbate the volatilization loss of the raw material diphenyl carbonate, while also triggering thermal degradation and side reactions of the polymer chains, leading to increased terminal hydroxyl content, decreased impact strength, and increased performance fluctuations in the product. Although existing technologies attempt to improve these problems by adjusting individual method parameters, they often fail to accurately grasp the intrinsic relationships between each reaction stage, resulting in a trade-off between different aspects and making it difficult to effectively control raw material consumption while improving product toughness.
[0005] Therefore, developing a non-phosgene melt transesterification method for preparing polycarbonate that can significantly reduce raw material consumption while ensuring high impact strength of the product is of great practical significance for meeting the material performance requirements of high-end applications and promoting the green upgrading of polycarbonate production technology. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention proposes a method for preparing polycarbonate using a non-phosgene melt transesterification process, and the resulting polycarbonate. By controlling the prepolymerization reaction conditions and the intrinsic viscosity of the prepolymer, this invention provides an innovative solution for synergistically optimizing high impact strength and low raw material loss in the product.
[0007] The first objective of this invention is achieved through the following technical solution:
[0008] A method for preparing polycarbonate without phosgene melt transesterification includes the following steps:
[0009] (1) Diphenyl carbonate and bisphenol A are mixed at a molar ratio of 1.02-1.08:1 and subjected to transesterification to obtain oligomers;
[0010] (2) The oligomer is subjected to prepolymerization reaction in a prepolymerization reactor at a temperature of 250-260℃ and a pressure of 3-5 kPa for a reaction residence time of 80-110 minutes to obtain a prepolymer with an intrinsic viscosity of 0.16-0.34 dL / g;
[0011] (3) The prepolymer is subjected to a first polycondensation reaction to obtain a first polycondensation product;
[0012] (4) The first polycondensation product is subjected to a final polycondensation reaction to obtain polycarbonate.
[0013] Preferably, the gas phase generated by the transesterification reaction is collected under vacuum and then enters a separation tower, and the diphenyl carbonate collected from the separation tower accounts for 2-4 wt% of the total feed mass of diphenyl carbonate.
[0014] More preferably, the gas phase generated by the transesterification reaction is collected under vacuum and then enters a separation tower, and the diphenyl carbonate collected from the separation tower accounts for 3.5-4.0 wt% of the total feed mass of diphenyl carbonate.
[0015] Preferably, the weight-average molecular weight of the prepolymer is 4500-10000 g / mol.
[0016] More preferably, the weight-average molecular weight of the prepolymer is 7000-8000 g / mol.
[0017] Preferably, the prepolymer has a terminal hydroxyl content of less than 500 ppmw, where ppmw represents parts per million by mass based on the total mass of the prepolymer.
[0018] More preferably, the prepolymer has a terminal hydroxyl content of 350-450 ppmw.
[0019] Preferably, the residence time of the pre-condensation reaction is 100-105 minutes.
[0020] Preferably, in the prepolymerization stage, after the gas phase at the top of the prepolymerization reactor is separated by a separation tower, the diphenyl carbonate collected accounts for 0.6-1.5 wt% of the total initial feed mass of diphenyl carbonate.
[0021] More preferably, in the pre-polymerization stage, after the gas phase at the top of the pre-polymerization reactor is separated by a separation tower, the diphenyl carbonate collected accounts for 0.6-1.1 wt% of the total initial feed mass of diphenyl carbonate.
[0022] Preferably, the pressure of the first polycondensation reaction is 0.4-0.6 kPa.
[0023] More preferably, the pressure of the first polycondensation reaction is 0.55-0.6 kPa.
[0024] Preferably, the temperature of the first polycondensation reaction is 275-282°C.
[0025] More preferably, the temperature of the first polycondensation reaction is 278-280℃.
[0026] Preferably, the first polycondensation reaction takes 55-60 minutes.
[0027] Preferably, the temperature of the final polycondensation reaction is 290-293°C.
[0028] More preferably, the temperature of the final polycondensation reaction is 291-292°C.
[0029] Preferably, the pressure of the final polycondensation reaction is 0.1-0.2 kPa.
[0030] More preferably, the pressure of the final polycondensation reaction is 0.1-0.15 kPa.
[0031] Preferably, the final polycondensation reaction takes 40-45 minutes.
[0032] More preferably, the final polycondensation reaction takes 42-45 minutes.
[0033] Preferably, the total distillation loss of diphenyl carbonate during the preparation of polycarbonate is ≤4.7 wt%, where wt% is based on the total initial mass of diphenyl carbonate.
[0034] More preferably, the total distillation loss of diphenyl carbonate during the preparation of the polycarbonate is 4.2-4.7 wt%.
[0035] This scheme controls the prepolymerization temperature within the range of 250-260℃. Firstly, it ensures the thermal stability of bisphenol A, preventing its decomposition above 260℃ to generate impurities such as quinones and ethylpropenylphenol. These impurities are prevented from inducing molecular isomerization or chain rearrangement reactions during subsequent polymerization, thus disrupting the regular structure of the polymer chain. Simultaneously, this temperature range avoids excessively rapid transesterification reactions. According to the Arrhenius equation, the reaction rate at 270℃ is several times that at 250℃. Excessively rapid reaction rates can lead to excessive localized reactions and intensified reverse reactions, resulting in a polarized structure where high and low molecular weights coexist. Furthermore, the temperature gradient within industrial reactors is significantly amplified above 260℃, further exacerbating the structural inhomogeneity of the prepolymer. These structural defects manifest as decreased impact strength in the final product. By controlling the pressure at this temperature (3-5 kPa), we avoid excessive volatilization of diphenyl carbonate due to excessively low pressure, which could disrupt the molar balance of the reaction system. This also ensures the effective removal of phenol byproducts, shifting the reaction equilibrium to the right and promoting uniform chain growth. This creates conditions for obtaining a uniform prepolymer with an intrinsic viscosity of 0.16-0.34 dL / g. When the intrinsic viscosity of the prepolymer stabilizes within this window, it indicates that the prepolymer has reached an appropriate molecular weight and has a uniform structure. This lays a high-quality feed foundation for subsequent polycondensation, allowing for a mild pressure of 0.4-0.6 kPa for the first polycondensation and a suitable temperature of 290-293℃ and 0.1-0.2 kPa for the final polycondensation. This avoids the high-temperature, high-vacuum conditions required in traditional methods due to poor prepolymer quality, thus reducing the risk of polycarbonate chain degradation during the final polycondensation stage. This allows the regular structure formed during the precondensation stage to be retained in the final product, achieving a stable notched impact strength of 72 kJ / m. 2 above.
[0036] The second objective of this invention is achieved through the following technical solution:
[0037] A polycarbonate is prepared by the above-described non-phosgene melt transesterification method for preparing polycarbonate.
[0038] Preferably, the notched impact strength of the polycarbonate is ≥72 kJ / m. 2 .
[0039] More preferably, the notched impact strength of the polycarbonate is 72-75 kJ / m. 2 .
[0040] Preferably, the impact strength of the polycarbonate fluctuates within the range of 69-75 kJ / m. 2 .
[0041] More preferably, the impact strength of the polycarbonate fluctuates within the range of 70-75 kJ / m. 2 .
[0042] Preferably, the polycarbonate has a terminal hydroxyl content of 230-270 ppmw.
[0043] More preferably, the polycarbonate has a terminal hydroxyl content of 230-245 ppmw.
[0044] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0045] 1. This invention optimizes the temperature, pressure, and molar ratio of the prepolymer during the prepolymerization stage, thereby stabilizing the intrinsic viscosity of the prepolymer within an ideal window. This lays a high-quality feed foundation for subsequent polycondensation, significantly improving the notched impact strength of polycarbonate and effectively narrowing the product performance fluctuation range, thus providing dual protection for the product's toughness and consistency.
[0046] 2. While improving product performance, the method of the present invention controls the volatilization of diphenyl carbonate within a reasonable range by matching the temperature and pressure during the pre-condensation stage, which significantly reduces the loss of raw materials during the reaction process and effectively saves production costs.
[0047] 3. The polycarbonate product obtained by this invention has a low end hydroxyl content, a more regular polymer chain structure, and excellent thermal and processing stability, making it suitable for applications such as optics and electronics where high material purity is required.
[0048] 4. This invention starts from the source of prepolymerization, avoiding the degradation risk caused by the use of harsh conditions to remedy prepolymer quality fluctuations in traditional methods. The method is more gentle and controllable, which is conducive to the stable operation of industrial production.
[0049] 5. This invention solves the technical contradiction in the prior art where it is difficult to balance product performance and raw material consumption, and provides a practical and feasible technical solution for the industrial production of high-performance polycarbonate. Detailed Implementation
[0050] The following will provide a clear and complete description of the concept, specific structure, and technical effects of the present invention in conjunction with embodiments, so as to fully understand the purpose, solution, and effects of the present invention. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0051] The materials used in the embodiments and comparative examples of this invention are described below:
[0052] Bisphenol A: 99.91-99.95%; produced from the upstream bisphenol A unit of Zhejiang Petrochemical.
[0053] Diphenyl carbonate: 99.90-99.95%; produced from the upstream diphenyl carbonate unit of Zhejiang Petrochemical.
[0054] Catalysts: tetraethylammonium hydroxide and sodium hydroxide.
[0055] Testing and definition of key parameters:
[0056] Intrinsic viscosity test: The Ubbelohde viscometer method was used to dissolve the oligomer, prepolymer or polycarbonate sample in dichloromethane to prepare a solution with a concentration of 0.5 g / dL. The outflow time of the solution was measured in a constant temperature water bath at 25℃, and the intrinsic viscosity value was calculated according to the empirical formula.
[0057] Weight-average molecular weight determination: The relative molecular mass distribution and residual monomer content of the sample were determined using an Agilent Technologies 1260 liquid chromatograph. When determining the relative molecular mass distribution, the mobile phase was tetrahydrofuran, the flow rate was 1 mL / min, the detection temperature was 40 ℃, the injection volume was 10 μL, the standard was polystyrene (PS), the polymerization rate constant (K) was 0.00049 mL / g, and the degree of polymerization (α) was 0.67.
[0058] Hydroxyl group content determination: A Bruker Avance NEO 600 MHz nuclear magnetic resonance spectrometer was used. The spectral width was set to 20 ppmw (-2 to 18 ppmw). The relaxation delay D1 was set to 60 s, the number of scans NS=128, and the solvent was deuterated chloroform. Unless otherwise stated, the ppmw of the terminal hydroxyl group content in this application represents parts per million (ppmw) based on the total mass of the corresponding polymer sample.
[0059] Diphenyl carbonate distillation loss determination: The top gaseous distillates from the transesterification reactor, prepolymerization reactor, first polymerization reactor, and final polymerization reactor were collected separately, condensed, and then sent to a separation tower for separation. The mass of diphenyl carbonate separated from the distillates of each reactor was measured, and the mass percentage (wt%) of the loss at each stage relative to the total initial feed mass of diphenyl carbonate was calculated. The sum of the losses at each stage is the total distillation loss of diphenyl carbonate.
[0060] Notched impact strength test: The test was conducted according to the ASTM D256 standard. The samples were injection molded into notched impact specimens and tested after being conditioned at 23°C and 50% relative humidity for 48 hours. The average value of 5 parallel samples was taken.
[0061] The polycarbonate described in this invention is prepared via a non-phosgene melt transesterification method. First, diphenyl carbonate and bisphenol A are mixed at the molar ratios shown in Table 1 and subjected to transesterification in a transesterification reactor to obtain an oligomer with an intrinsic viscosity of 0.05-0.09 dL / g. The obtained oligomer is then fed into a prepolymerization reactor and subjected to prepolymerization at the prepolymerization temperature, prepolymerization pressure, and prepolymerization residence time shown in Table 1 to obtain a prepolymer with an intrinsic viscosity of 0.16-0.34 dL / g, a weight-average molecular weight of 4500-10000 g / mol, and a terminal hydroxyl content of less than 500 ppmw. The obtained prepolymer is then heated to 275-282°C via a heat exchanger and fed into a first polypolymerization reactor, where it reacts at a pressure of 0.5 kPa for 60 minutes to obtain the first polypolymerization product. The first polycondensation product was fed into the final polycondensation reactor and reacted according to the final polycondensation temperature and final polycondensation pressure shown in Table 1. The final polycondensation time was fixed at 45 minutes to obtain the polycarbonate product.
[0062] The variation parameters (feed molar ratio, prepolymerization temperature, prepolymerization pressure, prepolymerization residence time, final polymerization temperature, and final polymerization pressure) of each embodiment and comparative example are detailed in Table 1.
[0063] Table 1. Preparation parameters of Examples 1-12 and Comparative Examples 1-12
[0064]
[0065] Example 1
[0066] The polycarbonate in Example 1 was prepared using the following steps:
[0067] (1) Diphenyl carbonate and bisphenol A were mixed at a molar ratio of 1.05:1 and transesterified in a transesterification reactor to obtain an oligomer with an intrinsic viscosity of 0.07 dL / g;
[0068] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 4 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.24 dL / g, weight average molecular weight of 7300 g / mol and terminal hydroxyl content of 400 ppmw.
[0069] (3) The prepolymer obtained in step (2) is heated to 280°C by a heat exchanger and then fed into the first polycondensation reactor. It is reacted for 60 minutes at a pressure of 0.5 kPa to obtain the first polycondensation product.
[0070] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 292°C and a pressure of 0.1 kPa for 45 minutes to obtain the polycarbonate product.
[0071] Example 2
[0072] The difference between Example 2 and Example 1 is that the pre-condensation residence time in step (2) is different; the other steps are the same as in Example 1.
[0073] (1) Proceed according to step (1) of Example 1;
[0074] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 4 kPa. The residence time is controlled at 80 minutes to obtain a prepolymer with intrinsic viscosity of 0.20 dL / g, weight average molecular weight of 6500 g / mol and terminal hydroxyl content of 440 ppmw.
[0075] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Example 2 was obtained.
[0076] Example 3
[0077] The difference between Example 3 and Example 1 is that the pre-polymerization residence time in step (2) is different; the other steps are the same as in Example 1.
[0078] (1) Proceed according to step (1) of Example 1;
[0079] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 4 kPa. The residence time is controlled to be 110 minutes to obtain a prepolymer with intrinsic viscosity of 0.28 dL / g, weight average molecular weight of 7900 g / mol and terminal hydroxyl content of 370 ppmw.
[0080] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Example 3 was obtained.
[0081] Example 4
[0082] The difference between Example 4 and Example 1 is that the pre-condensation temperature in step (2) is different; the other steps are the same as in Example 1.
[0083] (1) Proceed according to step (1) of Example 1;
[0084] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 250℃ and a pressure of 4 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.22 dL / g, weight average molecular weight of 6900 g / mol, and terminal hydroxyl content of 420 ppmw.
[0085] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Example 4 was obtained.
[0086] Example 5
[0087] The difference between Example 5 and Example 1 is that the pre-condensation temperature in step (2) is different; the other steps are the same as in Example 1.
[0088] (1) Proceed according to step (1) of Example 1;
[0089] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 260℃ and a pressure of 4 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.26 dL / g, weight average molecular weight of 7700 g / mol, and terminal hydroxyl content of 380 ppmw.
[0090] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Example 5 was obtained.
[0091] Example 6
[0092] The difference between Example 6 and Example 1 is that the pre-polymerization pressure in step (2) is different; the other steps are the same as in Example 1.
[0093] (1) Proceed according to step (1) of Example 1;
[0094] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 3 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.25 dL / g, weight average molecular weight of 7400 g / mol and terminal hydroxyl content of 430 ppmw.
[0095] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Example 6 was obtained.
[0096] Example 7
[0097] The difference between Example 7 and Example 1 is that the pre-polymerization pressure in step (2) is different; the other steps are the same as in Example 1.
[0098] (1) Proceed according to step (1) of Example 1;
[0099] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 5 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.23 dL / g, weight average molecular weight of 7200 g / mol and terminal hydroxyl content of 430 ppmw.
[0100] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Example 7 was obtained.
[0101] Example 8
[0102] The difference between Example 8 and Example 1 is that the molar ratio of the feed is different in step (1), while the other steps are the same as in Example 1:
[0103] (1) Diphenyl carbonate and bisphenol A were mixed at a molar ratio of 1.02:1 and transesterified in a transesterification reactor to obtain an oligomer with an intrinsic viscosity of 0.06 dL / g;
[0104] (2-4) Following the steps (2-4) of Example 1, the polycarbonate of Example 8 was obtained.
[0105] Example 9
[0106] The difference between Example 9 and Example 1 is that the molar ratio of the feed is different in step (1), while the other steps are the same as in Example 1:
[0107] (1) Diphenyl carbonate and bisphenol A were mixed at a molar ratio of 1.08:1 and transesterified in a transesterification reactor to obtain an oligomer with an intrinsic viscosity of 0.08 dL / g;
[0108] (2-4) Following the steps (2-4) of Example 1, the polycarbonate of Example 9 was obtained.
[0109] Example 10
[0110] The difference between Example 10 and Example 1 is that the final polycondensation temperature is different in step (4), while the other steps are the same as in Example 1:
[0111] (1-3) Proceed according to steps (1-3) of Example 1;
[0112] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 290°C and a pressure of 0.1 kPa for 45 minutes to obtain the polycarbonate product.
[0113] Example 11
[0114] The difference between Example 11 and Example 1 is that the final polycondensation temperature is different in step (4), while the other steps are the same as in Example 1:
[0115] (1-3) Proceed according to steps (1-3) of Example 1;
[0116] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 293°C and a pressure of 0.1 kPa for 45 minutes to obtain the polycarbonate product.
[0117] Example 12
[0118] The difference between Example 12 and Example 1 is that the final polycondensation pressure in step (4) is different; the other steps are the same as in Example 1.
[0119] (1-3) Proceed according to steps (1-3) of Example 1;
[0120] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 292°C and a pressure of 0.2 kPa for 45 minutes to obtain the polycarbonate product.
[0121] Comparative Example 1
[0122] The difference between Comparative Example 1 and Example 1 lies in the pre-condensation residence time in step (2), while the other steps are the same as in Example 1:
[0123] (1) Proceed according to step (1) of Example 1;
[0124] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 4 kPa. The residence time is controlled at 70 minutes to obtain a prepolymer with intrinsic viscosity of 0.15 dL / g, weight average molecular weight of 4200 g / mol and terminal hydroxyl content of 630 ppmw.
[0125] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Comparative Example 1 was obtained.
[0126] Comparative Example 2
[0127] The difference between Comparative Example 2 and Example 1 lies in the pre-condensation residence time in step (2), while the other steps are the same as in Example 1:
[0128] (1) Proceed according to step (1) of Example 1;
[0129] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 4 kPa. The residence time is controlled to be 130 minutes to obtain a prepolymer with intrinsic viscosity of 0.36 dL / g, weight average molecular weight of 9300 g / mol and terminal hydroxyl content of 520 ppmw.
[0130] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Comparative Example 2 was obtained.
[0131] Comparative Example 3
[0132] The difference between Comparative Example 3 and Example 1 is that the pre-polymerization pressure in step (2) is different; the other steps are the same as in Example 1.
[0133] (1) Proceed according to step (1) of Example 1;
[0134] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 2 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.25 dL / g, weight average molecular weight of 7400 g / mol and terminal hydroxyl content of 510 ppmw.
[0135] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Comparative Example 3 was obtained.
[0136] Comparative Example 4
[0137] The difference between Comparative Example 4 and Example 1 lies in the pre-polymerization pressure in step (2), while the other steps are the same as in Example 1:
[0138] (1) Proceed according to step (1) of Example 1;
[0139] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 255℃ and a pressure of 0.25 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.27 dL / g, weight average molecular weight of 7600 g / mol and terminal hydroxyl content of 550 ppmw.
[0140] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Comparative Example 4 was obtained.
[0141] Comparative Example 5
[0142] The difference between Comparative Example 5 and Example 1 is that the pre-condensation temperature in step (2) is different; the other steps are the same as in Example 1.
[0143] (1) Proceed according to step (1) of Example 1;
[0144] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 240℃ and a pressure of 4 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.18 dL / g, weight average molecular weight of 5800 g / mol, and terminal hydroxyl content of 520 ppmw.
[0145] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Comparative Example 5 was obtained.
[0146] Comparative Example 6
[0147] The difference between Comparative Example 6 and Example 1 is that the pre-condensation temperature in step (2) is different; the other steps are the same as in Example 1.
[0148] (1) Proceed according to step (1) of Example 1;
[0149] (2) The oligomer obtained in step (1) is fed into a prepolymerization reactor and prepolymerization reaction is carried out at a temperature of 270℃ and a pressure of 4 kPa. The residence time is controlled at 95 minutes to obtain a prepolymer with intrinsic viscosity of 0.32 dL / g, weight average molecular weight of 8800 g / mol, and terminal hydroxyl content of 540 ppmw.
[0150] (3-4) Following the steps (3-4) of Example 1, the polycarbonate of Comparative Example 6 was obtained.
[0151] Comparative Example 7
[0152] The difference between Comparative Example 7 and Example 1 is that the molar ratio of the feed in step (1) is different; the other steps are the same as in Example 1.
[0153] (1) Diphenyl carbonate and bisphenol A were mixed at a molar ratio of 1.10:1 and transesterified in a transesterification reactor to obtain an oligomer with an intrinsic viscosity of 0.07 dL / g;
[0154] (2-4) Following the steps (2-4) of Example 1, the polycarbonate of Comparative Example 7 was obtained.
[0155] Comparative Example 8
[0156] The difference between Comparative Example 8 and Example 1 is that the molar ratio of the feed in step (1) is different; the other steps are the same as in Example 1.
[0157] (1) Diphenyl carbonate and bisphenol A were mixed at a molar ratio of 1.01:1 and transesterified in a transesterification reactor to obtain an oligomer with an intrinsic viscosity of 0.06 dL / g;
[0158] (2-4) Following the steps (2-4) of Example 1, the polycarbonate of Comparative Example 8 was obtained.
[0159] Comparative Example 9
[0160] The difference between Comparative Example 9 and Example 1 is that the final polycondensation temperature in step (4) is different; the other steps are the same as in Example 1.
[0161] (1-3) Proceed according to steps (1-3) of Example 1;
[0162] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 285°C and a pressure of 0.1 kPa for 45 minutes to obtain the polycarbonate product.
[0163] Comparative Example 10
[0164] The difference between Comparative Example 10 and Example 1 is that the final polycondensation temperature is different in step (4), while the other steps are the same as in Example 1:
[0165] (1-3) Proceed according to steps (1-3) of Example 1;
[0166] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 300°C and a pressure of 0.1 kPa for 45 minutes to obtain the polycarbonate product.
[0167] Comparative Example 11
[0168] The difference between Comparative Example 11 and Example 1 is that the final polycondensation pressure in step (4) is different; the other steps are the same as in Example 1.
[0169] (1-3) Proceed according to steps (1-3) of Example 1;
[0170] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 292°C and a pressure of 0.05 kPa for 45 minutes to obtain the polycarbonate product.
[0171] Comparative Example 12
[0172] The difference between Comparative Example 12 and Example 1 is that the final polycondensation pressure in step (4) is different; the other steps are the same as in Example 1.
[0173] (1-3) Proceed according to steps (1-3) of Example 1;
[0174] (4) The first polycondensation product obtained in step (3) is fed into the final polycondensation reactor and reacted at a temperature of 292°C and a pressure of 0.25 kPa for 45 minutes to obtain the polycarbonate product.
[0175] Table 2 Performance test results of Examples 1-12 and Comparative Examples 1-12
[0176]
[0177] The test results show that, in Examples 1-12 of the preferred process parameters of this invention, the intrinsic viscosity of the prepolymer is stable at 0.16-0.34 dL / g, the terminal hydroxyl content is strictly controlled at 350-450 ppmw, the notched impact strength of the final polycarbonate product is stable at ≥72 kJ / m², the terminal hydroxyl content is 230-250 ppmw, and the total distillation loss of diphenyl carbonate is ≤4.7wt%, achieving synergistic optimization of high toughness, low terminal hydroxyl content, and low raw material loss.
[0178] By comparing Examples 1-3 with Comparative Examples 1 and 2, it can be seen that when the prepolymerization residence time is too short, the degree of polymerization of the prepolymer is insufficient, the intrinsic viscosity and weight-average molecular weight are low, and the content of terminal hydroxyl groups is significantly increased. This makes it difficult for subsequent polycondensation to make up for the molecular chain growth, resulting in a decrease in the impact strength of the product and an increase in DPC loss. When the prepolymerization residence time is too long, although the intrinsic viscosity of the prepolymer increases, the control effect of terminal hydroxyl groups becomes worse, and the impact strength of the product still decreases. This shows that the longer the prepolymerization time, the better. Only by controlling the residence time within an appropriate range can the molecular weight growth of the prepolymer and the stability of the end group structure be balanced.
[0179] By comparing Examples 1, 4, and 5 with Comparative Examples 5 and 6, it can be seen that when the prepolymerization temperature is too low, the transesterification and polycondensation reactions are not advanced enough, the content of terminal hydroxyl groups in the prepolymer is too high, and the impact strength of the final product is reduced. When the prepolymerization temperature is too high, although the molecular weight of the prepolymer is increased, the side reactions and material losses are aggravated, the content of terminal hydroxyl groups in the prepolymer increases, and the impact strength of the product and the control effect of terminal hydroxyl groups are both worse. This indicates that controlling the prepolymerization temperature at 250-260℃ is beneficial to achieving a balance between reactivity and structural stability.
[0180] By comparing Examples 1, 6, and 7 with Comparative Examples 3 and 4, it can be seen that when the prepolymerization pressure is too low, diphenyl carbonate in the system is more easily carried out with the gas phase, the raw material ratio balance is disrupted, the content of terminal hydroxyl groups in the prepolymer increases, the impact strength of the product decreases significantly, and the total loss of DPC increases. In particular, when the pressure is further reduced, the impact strength of the product decreases more significantly, indicating that the prepolymerization stage cannot simply rely on increasing the vacuum degree to promote the reaction, but should ensure the removal of by-products while avoiding excessive loss of DPC.
[0181] By comparing Examples 1, 8, and 9 with Comparative Examples 7 and 8, it can be seen that when the molar ratio of feed is too low, there is insufficient diphenyl carbonate in the system, the end-group control effect is worse, and the impact strength of the product decreases. When the molar ratio of feed is too high, the excess DPC not only increases volatilization loss, but also affects the end-group balance of the reaction system, resulting in a decrease in product performance. This indicates that an appropriate molar ratio of feed can ensure the smooth progress of the reaction and maintain a good balance between high impact strength and low feed loss.
[0182] By comparing Examples 1, 10, and 11 with Comparative Examples 9 and 10, it can be seen that when the final polycondensation temperature is too low, the polycondensation reaction is not advanced enough, the hydroxyl content at the product end is too high, and the impact strength is reduced. When the final polycondensation temperature is too high, the polymer chain segments are more prone to thermal degradation or side reactions, the hydroxyl content at the product end is further increased, and the impact strength is significantly reduced. This indicates that an appropriate final polycondensation temperature can both promote molecular chain growth and avoid the adverse effects of high temperature on the polycarbonate structure.
[0183] By comparing Examples 1 and 12 with Comparative Examples 11 and 12, it can be seen that when the final polycondensation pressure is too low, the DPC loss increases, the hydroxyl content at the product end increases, and the impact strength decreases; when the final polycondensation pressure is too high, the by-products are not removed sufficiently, the polycondensation reaction is limited, the hydroxyl content at the product end is still too high, and the impact performance is also difficult to maintain. This indicates that the final polycondensation pressure needs to be matched with the quality of the upstream prepolymer. Too high or too low pressure will weaken the overall performance of the product.
[0184] In summary, the technical effect of this invention is not produced by a single isolated condition, but rather by the synergistic control of temperature, pressure, residence time, and feed molar ratio during the prepolymerization stage. This first yields a prepolymer with moderate intrinsic viscosity, stable molecular weight, and low terminal hydroxyl content. Then, combined with mild and effective final polymerization conditions, the final polycarbonate simultaneously possesses high notched impact strength, low terminal hydroxyl content, and low DPC loss. Each comparative example, after deviation from a single factor, showed varying degrees of increase in terminal hydroxyl content, decrease in impact strength, or increase in DPC loss, further demonstrating the clear necessity and stable comprehensive advantages of the process parameter combination of this invention.
[0185] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A method for preparing polycarbonate without phosgene melt transesterification, characterized in that, Includes the following steps: (1) Diphenyl carbonate and bisphenol A are mixed at a molar ratio of 1.02-1.08:1 and subjected to transesterification to obtain oligomers; (2) The oligomer is subjected to prepolymerization reaction in a prepolymerization reactor at a temperature of 250-260℃ and a pressure of 3-5kPa for a reaction residence time of 80-110 minutes to obtain a prepolymer with an intrinsic viscosity of 0.16-0.34dL / g, the weight average molecular weight of the prepolymer is 4500-10000g / mol, and the terminal hydroxyl content of the prepolymer is less than 500ppmw; (3) The prepolymer is subjected to a first polycondensation reaction to obtain a first polycondensation product; (4) The first polycondensation product is subjected to a final polycondensation reaction at a temperature of 290-293℃ and a pressure of 0.1-0.2kPa to obtain polycarbonate.
2. The method for preparing polycarbonate by non-phosgene melt transesterification according to claim 1, characterized in that, The residence time for the pre-condensation reaction is 100-105 minutes.
3. The method for preparing polycarbonate by non-phosgene melt transesterification according to claim 1, characterized in that, The pressure of the first polycondensation reaction is 0.4-0.6 kPa.
4. The method for preparing polycarbonate by non-phosgene melt transesterification according to claim 1, characterized in that, The temperature of the first polycondensation reaction is 275-282℃.
5. The method for preparing polycarbonate by non-phosgene melt transesterification according to claim 1, characterized in that, The first polycondensation reaction takes 55-60 minutes.
6. The method for preparing polycarbonate by non-phosgene melt transesterification according to claim 1, characterized in that, The final polycondensation reaction takes 40-45 minutes.
7. A polycarbonate, characterized in that, The polycarbonate was prepared by the non-phosgene melt transesterification method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Device and method for preparing aromatic polycarbonate
CN108948339A
Preparation method and application of high-molecular-weight hydrogenated bisphenol A polycarbonate
CN117567734A
Preparation method of high-temperature-resistant basement membrane for IME technology
CN118290716A